2017
DOI: 10.1155/2017/3685402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Partnership Care Model on Mental Health of Patients with Thalassemia Major

Abstract: Background Thalassemia major has become a public health problem worldwide, particularly in developing and poor countries, while the role of educating the family and community has not been considered enough in patients' care. Objectives This study examines the impact of partnership care model on mental health of patients with beta-thalassemia major. Materials and Methods This experimental study, with pretest and posttest design, was performed on patients with beta-thalassemia major in Jiroft city. 82 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Blood transfusion and standard ironchelation therapy are common alleviating treatments against β-thalassaemia, even though the treatment technology for improving the ineffective production of red blood cells and the technique for regulating globin imbalance are progressing [10,11]. However, the need for regular blood transfusions and developmental abnormalities in children with β-thalassaemia seriously affect their mental health [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood transfusion and standard ironchelation therapy are common alleviating treatments against β-thalassaemia, even though the treatment technology for improving the ineffective production of red blood cells and the technique for regulating globin imbalance are progressing [10,11]. However, the need for regular blood transfusions and developmental abnormalities in children with β-thalassaemia seriously affect their mental health [12].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated the statistical correlation between β-thalassaemia and the incidence of psychological morbidity, especially in children and adolescents [12]. It has been reported that transfusion-dependent β-thalassaemia significantly impacts the life quality of paediatric and adolescent patients in upper Egypt, and the same disease also causes considerable psychological issues for patients in Sri Lanka [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with TM, due to the nature of their disease, are exposed to several physical and psychological problems. 33 Because happiness training based on the Fordyce approach has a cognitive-behavioural aspect, it can help these patients to first identify their uncomfortable thoughts and behaviours and then employ cognitive-behavioural management programmes to change the situation. In addition, focusing on life’s negative aspects and persistent emotional unhappiness can have destructive effects on the body’s physiological system and disrupt the immune system functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Dashtban et al (2021) reported that family-centered empowerment program intervention has considerably improved the HRQoL for children with thalassemia. Similar studies show that family empowerment programs and partnership care models improve HRQoL among these children and their families by increasing parental awareness and attitude about the disease (Allahyari et al, 2006;Shamsi et al, 2017;Wacharasin et al, 2015).…”
Section: Introductionmentioning
confidence: 90%